Kauza hornické důchody v reformě z roku 2016, odůvodněnost zvláštního důchodového věku - Štefko, Martin (Časopis pro právní vědu a praxi, 2018)
This Article deals with reform of early miners’ old age pensions that occurred in 2016 (miners can retire up to 7 (in some cases even 10) years before standard retirement age and their amounts are above standards compared to other insureds). The government impaired public benefits-defined pay-as-you-go pension insurance on behalf of narrow occupationally and aged defined group of insureds. The article analyses not only reforms’ justification both official and informal, but proclaimed by decision holders but considers the collision of principle of something for something (deservingness) and affirmative actions to low-paid and hard-working insureds that are intended to stop preservation of in-work discrimination even in after-retirement life.